Fertilizer Policy Development in Nepal - Shrestha, Ram Krishna (Journal of Agriculture and Environment, 2010)
Fertilizer is a vital input for agriculture production. With the growing popularity of modern agriculture, fertilizer consumption in Nepal has been increasing over the years. Since, Nepal does not produce any fertilizers, demand for fertilizers are being met through formal and informal imports. Over the years, fertilizer policy changes have been observed several times in a bid to satisfy farmers' demand for quality fertilizers. While fertilizer policy change of deregulating the fertilizer trade initially produced positive impact in overall supply situation, deregulation policy could not largely ensure the supply of quality fertilizers in required quantity and time. Re-introducing subsidy regime in chemical fertilizer by the government's recent decision could be considered as a positive development towards meeting farmers demand for quality fertilizer. However, given the quota of subsidized fertilizer, which is far less than the actual demand, the problem of supply is likely to continue. To address current problem of short supply government should increase the quota at least up to three hundred thousand metric tons. Moreover, Ministry of Agriculture and Cooperatives should come up with a long-term plan aiming at sustainable management of soil fertility. Key words: Fertilizer subsidy; Fertilizer deregulation; Fertilizer import The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 126-137 Uploaded date: 16 September, 2010